2017
DOI: 10.1111/liv.13557
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus as a cause of acute hepatitis acquired in Switzerland

Abstract: Nucleic acid-based diagnosis reveals HEV as a relevant cause of acute hepatitis in Switzerland. Middle-aged and elderly men constitute the majority of symptomatic patients. Testing for HEV should be included early in the diagnostic workup of acute hepatitis and of neuralgic amyotrophy, a typical extrahepatic manifestation of HEV genotype 3 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
1
30
0
1
Order By: Relevance
“…Some of these cases have been reported in previous studies with different aims. 25,26 Age, sex, immunosuppression status, ALT, and bilirubin levels of the overall cohort at onset are summarized in table 1. The median age was 59 years, with a nonsignificant predominance of men (59% vs 41%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these cases have been reported in previous studies with different aims. 25,26 Age, sex, immunosuppression status, ALT, and bilirubin levels of the overall cohort at onset are summarized in table 1. The median age was 59 years, with a nonsignificant predominance of men (59% vs 41%).…”
Section: Resultsmentioning
confidence: 99%
“…Sera from patients with suspected HEV infection were tested for HEV IgG and IgM with Dia.Pro kits (Diagnostic Bioprobes srl, Italy). Real-time quantitative HEV RNA reverse transcriptase polymerase chain reaction and HEV genotype determination were performed according to Fraga et al 25 Glossary ALT = alanine aminotransferase; ANA = antinuclear antibodies; CK = creatinine kinase; GBS = Guillain-Barré syndrome; HEV = hepatitis E virus; IFN = interferon; IVIg = intravenous immunoglobulin; NA = neuralgic amyotrophy.…”
Section: Virologic Analysesmentioning
confidence: 99%
“…France [ 11 ], the UK [ 12 ] and Germany [ 13 ]. It is the converse in Switzerland, notwithstanding a steady increase in demand for molecular testing, the proportion of positive HEV samples has remained roughly constant over the years from 2011 to 2016 [ 14 ]. HEV circulation in Italy was demonstrated since the 1980s and sporadic autochthonous incident cases have been reported for several years [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human-to-human transmission may occur but seems to be rare; however, blood transfusion has been reported as a transmission pathway [82]. In humans, most infections seem to be subclinical; the most severe clinical sings are observed in older males and patients with pre-existing liver diseases or increased alcohol consumption [83,84]. A meta-analysis of 432 studies on the HEV seroprevalence in humans in Europe from 2003 to 2015 showed a wide range from 0.6 to 52.5%.…”
Section: Hepatitis E Virus Genotypes 3 Andmentioning
confidence: 99%